Effect of deficit irrigation under furrow irrigation techniques on garlic (Allium sativum L.) productivity at the central highland of Ethiopia - Biruk Getaneh Ayele; Shemelies Asseffa; Abraham Woldemichael Tuhar (Water-Energy Nexus, 2023)
Garlic is one of the widely grown vegetables in irrigation but poor irrigation management causes depressed agronomic practices and results in low productivity. Therefore, this study aimed to investigate the effect of deficit irrigation on soil moisture, yield, and water use efficiency (WUE) of garlic (Allium sativum L.) local cultivars under furrow irrigation techniques. It was laid out in Randomized Complete Block Design (RCBD) with three replications with four irrigation levels (100, 85, 70, and 55% ETc) and three furrow techniques namely: Alternative (AFI), Fixed (FFI) and Conventional (CFI). An irrigation regime was determined based on both ETc and soil moisture methods. All collected data were subjected to ANOVA by SAS statistical software. The result showed that yield and WUE were highly significantly (p < 0.01) affected by deficit levels and furrow techniques. The maximum yield of 8.9 t/ha was obtained with the application of 100% ETc under CFI, while the maximum CWUE of 4.1 kg/m3 with the application of 55% ETc under AFI. The application of 85% ETc under AFI resulted in optimum yield and CWUE. Correlation analysis revealed that strong positive association between garlic yield and its yield components. In areas where there is abundant water, garlic could be irrigated with a seasonal irrigation depth of 592 mm (100% ETc) under CFI techniques. The application of 85% ETc under AFI techniques saves irrigation water with insignificant yield reduction and this saved water could possibly produce an extra yield of 7.1 t/ha, resulting in a more economical return with a marginal rate of return (MRR) of 1463%. Therefore, it is the best choice under the conditions of the study area and other similar areas.